Strategi Guru Fikih dalam Menggunakan Media Pembelajaran Berbasis Information and Communication Technology (ICT) di MTsS Hubbul Wathan Modal Bangsa Sei Bingai - Haidir, Haidir; Baiti, Nanda Nurul; Manalu, Sri Rahmayani; Nova, Andre; Anwar, Hairil; Septian, Yuhdi (EduInovasi: Journal of Basic Educational Studies, 2024)
Teachers use learning strategies to ensure that learning goes well, efficiently and optimally. After carrying out the evaluation, the teacher carries out follow-up to achieve the minimum standard of student completeness. This study aims to explain how teachers use teaching strategies in the classroom. The research conducted obtained data through interviews and observations in class IX with several PAI subject teachers. The data validation method used is the triangulation technique. The data analysis technique consisted of data reduction (data selection), data presentation (data display), and then conclusion drawing/verification. The results showed that the teacher's strategy in teaching in class IX MTsS Hubbul Wathan Modal Bangsa in using strategies in class is good, this is evidenced by an orderly learning process, students' understanding that is easy to understand and accompanied by the use of IT-based media that helps students to deepen the material presented. Keywords: Strategy, Learning Media, Information Technology